Therapy response and prognosis of patients with early breast cancer with low positivity for hormone receptors: an analysis of 2765 patients from neoadjuvant clinical trials - Villegas, Sonia Lorena; Nekljudova, Valentina; Pfarr, Nicole; Engel, Jutta; Untch, Michael; Schrodi, Simone; Holms, Frank; Ulmer, Hans U.; Fasching, Peter A.; Weber, Karsten E.; Albig, Christian; Heinrichs, Clemens; et al. (European journal of cancer, 2021)
Aim - To evaluate HER2-negative breast cancer (BC) with a low hormone receptor (HR) expression, with regard to pathological complete response (pCR) and survival, in comparison to triple-negative BC (TNBC) and strong HR-positive BC. - Methods - We compared negative [oestrogen (ER) and progesterone receptor (PR) <1%], low-positive (ER and/or PR 1-9%) and strong-positive (ER or PR 10-100%) HR-expression in neoadjuvant clinical trial cohorts (n = 2765) of BC patients. End-points were disease-free survival (DFS), distant-disease free survival (DDFS) and overall survival (OS). We performed RNA sequencing on available tumour tissue samples from patients with low-HR expression (n = 38). - Results - Ninety-four (3.4%) patients had low HR-positive tumours, 1769 (64.0%) had strong HR-positive tumours, and 902 (32.6%) had TNBC. There were no significant differences in pCR rates between women with low HR-positive tumours (27.7%) and women with TNBC (35.5%). DFS and DDFS were also not different [for DFS, hazard ratio 1.26, 95%-CI (confidence interval) : 0.87-1.83, log-rank test p = 0.951; for DDFS, hazard ratio 1.17, 95%-CI: 0.78-1.76, log-rank test p = 0.774]. Patients with strong HR-positive tumours had a significantly lower pCR rate (pCR 9.4%; odds ratio 0.38, 95%-CI: 0.23-0.63), but better DFS (hazard ratio 0.48, 95%-CI: 0.33-0.70) and DDFS (hazard ratio 0.49, 95%-CI: 0.33-0.74) than patients with low HR-positive tumours. Molecular subtyping (RNA sequencing) of low HR-positive tumours classified these predominantly into a basal subtype (86.8%). - Conclusion - Low HR-positive, HER2-negative tumours have a similar clinical behaviour to TNBC showing high pCR rates and poor survival and also a basal-like gene expression signature. Patients with low HR-positive tumours should be regarded as candidates for therapy strategies targeting TNBC.